News Writing for Print - Ricky W. Telg (EDIS)
A good print news story will contain the following components: inverted pyramid structure, five Ws and H, leads, impersonal reporting, news writing techniques, quotations and attributions, Associated Press Style, and proper grammar and punctuation. This 5-page fact sheet was written by Ricky Telg, and published by the UF Department of Agricultural Education and Communication, January 2015.